2000
DOI: 10.1161/01.atv.20.5.1323
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cholesteryl Ester Transfer Protein– Taq IB Polymorphism With Variations in Lipoprotein Subclasses and Coronary Heart Disease Risk

Abstract: Abstract-Cholesteryl ester transfer protein (CETP) facilitates the exchange of triglycerides and cholesteryl esters between lipoprotein particles, a key step in reverse cholesterol transport in humans. Variations at the CETP locus have been shown to be determinants of the levels and activity of CETP and high density lipoprotein (HDL) plasma concentration. The associations of the common CETP polymorphism, TaqIB in intron 1, with lipoprotein levels and particle size distribution, CETP activity, and coronary hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
254
3
11

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(306 citation statements)
references
References 50 publications
38
254
3
11
Order By: Relevance
“…Furthermore, we have investigated the associations of the different alleles with clinical characteristics and lipid profiles in these patients. The frequency of the TaqIB polymorphism in this population was similar to that found in other studies, 7,15 suggesting that our study population is not genetically different from others. Our data clearly show an association of the B1 allele of CETP-TaqIB polymorphism with HDL-cholesterol levels at baseline.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, we have investigated the associations of the different alleles with clinical characteristics and lipid profiles in these patients. The frequency of the TaqIB polymorphism in this population was similar to that found in other studies, 7,15 suggesting that our study population is not genetically different from others. Our data clearly show an association of the B1 allele of CETP-TaqIB polymorphism with HDL-cholesterol levels at baseline.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, an odds ratio of 0.7 for CHD was found in male, but not in female, participants of the Framingham Offspring study. 7 In recently published studies, higher plasma CETP levels of FH patients were associated with a more atherogenic lipid profile. 18 -20 In one of these reports, the highest tertile of plasma CETP level was also associated with a higher increase of progression of atherosclerosis after 2 years of statin therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Several previous studies have demonstrated such associations for HDL-C, specifically with SNP4 (TaqIB). [3][4][5]8,[35][36][37] In some reports, the association was seen only in subgroups, such as ex-and nonsmokers, 38 or in women, but not in men. 39 Alhough we could not replicate the association of an increased baseline HDL-C in the presence of the mutant B2 allele of SNP4, the strong stepwise decrease in CETP mass and activity associated with the number of B2 alleles of SNP4 clearly underlines such an expected effect on HDL-C. With respect to SNP 7 (A373P) and SNP8 (R451Q), the Copenhagen City Heart Study found a decrease in HDL-C and ApoA1 in carriers of the mutant allele, both in men and women.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, other discrepant results were reported in distinct follow-up phases of the same study. In the Framingham Heart Study, both linear (43) and inverse (44) associations between plasma CETP activity and cardiovascular risk were reported. After a thorough search of the literature, we found incongruent results demonstrating both direct and inverse relationships as well as a lack of correlation between CETP levels or CETP genetic variants and atherosclerosis risk.…”
Section: Human Studiesmentioning
confidence: 99%